PEMBERDAYAAN PEREMPUAN PESISIR MELALUI PENGEMBANGAN DAN PENGUATAN PEREKONOMIAN BERBASIS KOMODITAS LOKAL - Desy Cahyaning Utami (LPPM Universitas Yudharta Pasuruan, 2018)
Coastal life is always characterized by poor people with a less stable economy. This is inversely proportional to marine resources that are filled with the wealth of fish and other biota. In addition to this, women's participation is still very minimal in managing existing resources. The existing reality shows that the ability, quality and productivity of women in the management of economic commodities keep the population around the coast still poor and underdeveloped. Local wisdom as an existing capital can provide an alternative alternative empowerment to be more targeted, so it needs to get more attention. Jarangan Village is one of the suppliers and producers of milkfish in Pasuruan, but unfortunately it is still constrained by the processing of milkfish itself. During this time milkfish are only sold in fresh form even though there are those that sell in the form of processed and made into crackers but are still constrained in production and marketing that cannot be continuous because they only produce when there are orders. It is expected that by providing training on various processed products from milkfish, one of them is the practice of making sticks and ice cream from milkfish can provide additional income for the people on Pasuruan's coast, especially for mothers in the village of Jarangan itself. The expected impact itself can help their household economy with productive businesses.